SOA-based Architecture for a Generic and Flexible E-assessment System - AL-Smadi, M.; Guetl, Christian (IEEE Computer Society, 2010)
In the last decade, universities and higher education institutes have become more and more interested in using computers to deliver their formative and summative assessments. Therefore, several computer-assisted-assessment systems have been developed. The variance in the application domains of e-assessment has a main influence on having different assessment systems in the same university. Since universities have different colleges and specializations based on their types and in order to deliver their assessment activities online, each college is developing or buying assessment system or tools based on its specializations and courses. This has caused some universities to have more than one computer-assisted-assessment system. In this paper, a service-oriented e-assessment system will be suggested to solve this problem. A service-oriented architecture for a generic and flexible assessment system will be provided with cross-domain use cases to show the flexibility of this architecture.